Empowering Women at Bottom of Pyramid through Microfinance - Sharma, Gunjan (International Journal of Psychosocial Rehabilitation, 2020)
Women are an essential part of society. Their empowerment is very a prime factor for the growth of the economy of the country. This study attempts to identify the most influencing and dominating factors of women empowerment of rural areas of western Uttar Pradesh in India. Rural women play a vital role to enhance the economy and eliminate social evil as gender inequality, society’s perception towards backward people. Women's empowerment plays an important role to eradicate poverty through microfinance. Microfinance provides a small number of loans to low-income people without any security. It helps to reduce unemployment and increase the motivation to become an entrepreneur. In this study, data were collected from one hundred eight rural women who involved in self-employment activities through a questionnaire using personal interviews. Convenience sampling technique was used to select the sample size from three villages of different districts in Uttar Pradesh. The exploratory factor analysis was performed on twenty-one variables for screening and reducing the variables to identify the influencing and dominating factors on women’s empowerment. The result of this study abridged the variables into eight factors as socio-economic factors, source of income, poverty eradication, microfinance awareness, personal empowerment, social empowerment, society’s perception and family empowerment.